Ultra fast frequency independent instantaneous power factor detector - Omran, Safaa S.; Al-Khalid, Ali. Sh.; Yaseen, Amer Atta (Institute of Advanced Engineering and Science, 2019)
Many schemes were attempted to lessenthe time taken for measuring the power factor of a linear load. This paper suggests taking advantage of a previous paper where only two samples of the voltage and current were adequate to have a very fast calculation method of the power factor. That scheme used a phase locked loop (PLL) as a frequency multiplier scheme to acquire two progressive samples of the voltage and current which are concurrent. The time elapsed for measurement was the reciprocal of the PLL sampling frequency; no further scheme was reported after that to claim a faster method. This paper gets use of that work to get two progressive samples of voltage and current separated by a short time. The scheme is frequency independent with an indication for lead lag. All the operations are executed by a PIC microcontroller rather than a computer with few support circuits. The output will be shown either in digital or analogue (DC) form. The percentage of error depends mainly on the resolution (number of bits) for both the ADC and DAC used.